Practical negotiating : tools, tactics, & techniques - Gosselin, Tom, 1948- (John Wiley & Sons, 2007)
Praise for Practical Negotiating: Tools, Tactics & Techniques"Practical Negotiating is an innovative, resourceful, and-as its name implies-practical guide to the art and science of negotiating. Unlike many books on negotiating, which are filled with theories and anecdotes, this one is rich with examples, tactics, and tips, which makes it the indispensable book when you are going into any negotiation."--Terry R. Bacon, President, Lore International Institute and author of What People Want: A Manager's Guide to Building Relationships That Work"There is something in this book for the most experien